The Vote Buying among Madurese Muslim; Islamic Law Standpoint - Yunita, I Made; Putu Sugiantiningsih, Anak Agung; Hidayaturrahman, Mohammad (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2024)
As one of the largest Muslim democracies, Indonesia is facing a significant challenge, one of which is vote-buying among its Muslim voters. It is believed that vote buying is a popular type of bribery practice or so-called risywah. This raises basic questions for this study, namely how the vote buying practice takes place, How the intermediaries or political brokers play their role, and how the practice has been perceived by Islamic scholars. Choosing Madura as the research locus and the 2024 legislative member election event, this study used direct observation and in-depth interviews with various stakeholders consisting of voters, the election committee, the supervisory committee, prospective legislative members, and the winning team. Apart from that, it also used document tracing, including documents from the General Election Commission and online media sources. The study's findings indicate that vote buying was orchestrated by a network of political brokers who shape the behavior of political actors and Muslim voters. It is reinforced by the increasing pragmatism and economic orientation of Muslim voters when choosing representative candidates and political parties. The most popular ones are through the wholesale and retail schemes. Meanwhile, from an Islamic law standpoint, ranging from hadith, and Islamic mass organizations to Islamic scholars, vote buying is undoubtedly agreed its unlawful status despite the belief that it is almost impossible to win an election without committing to vote buying.